2012
DOI: 10.5047/meep.2012.00101.0001
|View full text |Cite
|
Sign up to set email alerts
|

Tomography and Dynamics of Western-Pacific Subduction Zones

Abstract: We review the significant recent results of multiscale seismic tomography of the Western-Pacific subduction zones and discuss their implications for seismotectonics, magmatism, and subduction dynamics, with an emphasis on the Japan Islands. Many important new findings are obtained due to technical advances in tomography, such as the handling of complex-shaped velocity discontinuities, the use of various later phases, the joint inversion of local and teleseismic data, tomographic imaging outside a seismic netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 277 publications
3
61
0
Order By: Relevance
“…The first is that detailed studies of reflected and converted waves, as well as the first P-and Swaves, revealed the existence of the Conrad and Moho discontinuities and the upper boundary of the subducting Pacific slab beneath NE Japan (Fig. 2.1c), and the three discontinuities exhibit significant lateral depth variations (see the review by Zhao 2012). All the previous tomographic studies prior to 1990 (e.g., Aki and Lee 1976;Thurber 1983) could not handle the complex-shaped velocity discontinuities in the study area.…”
Section: Model Parameterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is that detailed studies of reflected and converted waves, as well as the first P-and Swaves, revealed the existence of the Conrad and Moho discontinuities and the upper boundary of the subducting Pacific slab beneath NE Japan (Fig. 2.1c), and the three discontinuities exhibit significant lateral depth variations (see the review by Zhao 2012). All the previous tomographic studies prior to 1990 (e.g., Aki and Lee 1976;Thurber 1983) could not handle the complex-shaped velocity discontinuities in the study area.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…All the previous tomographic studies prior to 1990 (e.g., Aki and Lee 1976;Thurber 1983) could not handle the complex-shaped velocity discontinuities in the study area. The second reason is that clear later phases (i.e., reflected and converted waves) associated with the three discontinuities were detected in the seismograms of local crustal earthquakes and intermediate-depth earthquakes in the subducting Pacific slab (see Zhao 2012 for the detailed review). These later-phase data contain important information on the Earth's structure, in particular, in and around velocity discontinuities, hence they should be used in tomographic inversion so that local earthquakes can be better located and a better 3-D velocity model can be obtained.…”
Section: Model Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since the pioneering works of Aki and Lee (1976) and Dziewonski et al (1977), tomographic images have provided crucial information for the understanding of plate tectonics, volcanism, and geodynamics (e.g., Romanowicz, 1991;Liu and Gu, 2012;Zhao, 2012). Seismic tomography itself has also gone through significant development over the last 3 decades, including advances in both methodology and data usage.…”
Section: Introductionmentioning
confidence: 99%
“…Subduction zones are convergent plate boundaries which are characterized geographically by deep ocean trenches and island arcs or continental margins; seismically by the most abundant and largest earthquakes and the dipping Wadati-Benioff zone of intermediate-depth and deep earthquakes; tectonically by extensive crustal faulting and mountain building; and magmatically by a trench-parallel linear belt of active volcanoes, i.e., the volcanic front (e.g., Zhao 2001aZhao , 2012. Plate subduction is a fundamental and unique process in terrestrial tectonics and geodynamics.…”
mentioning
confidence: 99%